Assessing Sustainability Initiatives in Higher Education Institutions - Yturzaeta, Justin Edric G. (Archīum Ateneo, 2023)
This study investigates how sustainability initiatives in higher education institutions (HEIs) can be assessed. As educational institutions, HEIs are more focused on the academic aspects of sustainability although many have also made strides to address environmental, social, and governance concerns. One assessment tool, developed based on Hart and Milstein’s (2003) Sustainable Value Framework, looks at the sustainability value of a HEI according to two dimensions: a temporal dimension that determines whether or not a HEI’s sustainability initiatives address either present concerns or long-term goals and an organizational boundary dimension that classifies the initiatives as responses to either the internal or external concerns of the organization. The tool gives a rapid sustainability assessment of HEIs and can help them manage their sustainability efforts to maximize the sustainable value created in their own special contexts. HEIs that are committed to mainstreaming sustainability can thus use the adapted conceptual framework as a means for both assessment and planning. For the purposes of this study, semi-structured interviews with nine private HEIs in Metro Manila were conducted to gather information about their current sustainability initiatives while sustainability context and content analysis was performed to determine their position within the assessment tool’s framework.